2021
DOI: 10.1016/j.ijsu.2021.106148
|View full text |Cite
|
Sign up to set email alerts
|

Changes in appendicitis treatment during the COVID-19 pandemic – A systematic review and meta-analysis

Abstract: Background During the COVID-19 pandemic in 2020 a decrease of emergency consultations and modification in treatment of numerous medical conditions were observed. Aim of this paper was to evaluate the effect of the COVID-19 pandemic on incidence, treatment strategies, severity, length of hospital stay and time of presentation in adults and children with acute appendicitis. Methods A systematic literature search of Pubmed, Embase and Cochrane databases was performed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
68
1
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 55 publications
11
68
1
9
Order By: Relevance
“…As per the findings from recent adult/pediatric studies, the patients developing appendicitis during the pandemic reach healthcare facilities on time (similar to the pre-pandemic period). Although an identical management algorithm of acute appendicitis was followed during the two time periods, more reliance on non-operative management was observed among the surgeons during the COVID-19 pandemic [ 69 , 70 ]. Our analysis shows the same result.…”
Section: Discussionmentioning
confidence: 99%
“…As per the findings from recent adult/pediatric studies, the patients developing appendicitis during the pandemic reach healthcare facilities on time (similar to the pre-pandemic period). Although an identical management algorithm of acute appendicitis was followed during the two time periods, more reliance on non-operative management was observed among the surgeons during the COVID-19 pandemic [ 69 , 70 ]. Our analysis shows the same result.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in AA treatment during the COVID-19 pandemic has been recently explored in two systematic reviews. [7] , [21] The number of studies identified by Köhler at al. [21] was lower compared to our work (46 vs. 54), in line with a literature search ended one month before (Feb 1 st vs. Mar 5 th 2021).…”
Section: Discussionmentioning
confidence: 99%
“… [7] , [21] The number of studies identified by Köhler at al. [21] was lower compared to our work (46 vs. 54), in line with a literature search ended one month before (Feb 1 st vs. Mar 5 th 2021). Similar to our findings, they demonstrated an overall significant reduction of AA cases by 21% in adults and an increase of 13% in children.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that acute abdominal pain, including appendicitis, is a condition that requires emergency (surgical) care, one would not expect a decrease in hospital admissions during the COVID-19 pandemic, yet multiple studies have demonstrated a significant decrease in referrals for acute appendicitis [ 5 – 9 ]. In addition, several studies have reported an increase in the proportion of complex acute appendicitis [ 6 , 8 16 ], as well as a prolonged time between onset of symptoms and hospital admission [ 8 , 10 – 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%